Дослідження поселення празько-корчацької культури у місті Рівному - Войтюк, О.П.; Прищепа, Б.А. (Археологія і давня історія України, 2021)
У статті введено до наукового обігу результати досліджень об’єктів ранніх слов’ян празько-корчацької культури на багатошаровому поселенні у південній частині міста Рівного. Це житло-напівземлянка з піччю-кам’янкою, господарська яма і вогнище, які, вірогідно, складали один житлово-господарський комплекс. Аналізується колекція ліпних глиняних горщиків із досліджених об’єктів. The paper introduces into scientific circulation the results of research of the objects of Early Slavs of the Prague-Korchak culture in a multi-layered settlement in the southern part of Rivne city. The settlement is located on the eastern shore of the Basiv Kut Reservoir, on the oval hill measuring 220 × 120 m. The first finds of the Early Middle Ages were discovered here by V. K. Piasetskyi in 1989. In 2019, the excavations were carried out on the area of 590 m2; the housing and storage pit of the Prague-Korchak culture have been discovered. The quadrangular foundation pit of 3.5 × 3.5 m square was sunk into the earth to the 0.3—0.4 m from detection level. The remains of stone stove made on the wooden frame were located in the northern corner of the dwelling. Such semi-dugout dwellings with the stove in one of corners was the main type of residential buildings in the population of the Prague-Korchak culture. The pillar holes found in the corners of the foundation pit and in the middle of the walls indicate the frame-pillar construction of the wooden walls. Among the stones from the destroyed stove and on the earthen floor in the central part of the foundation pit of the dwelling the remains of nine clay pots were found. We managed to reconstruct the full profiles of seven of them; two else vessels are represented by the profiles of the upper parts. The pots from the dwelling have a conical body, weakly marked shoulder, scarcely marked neck and short rim. The surface of the item is insufficiently smoothed and bumpy. The admixtures in the clay are mostly of small and medium size, with added fireclay, grus and sand. By their size the vessels are divided into small (1), medium (5) and large (3). All pots from the dwelling belong to variants 1—3 of the first type according to I. P. Rusanova’s classification. This combination is typical of the early monuments of the Prague-Korchak culture. The analysis allows attributing the ceramic complex from Rivne to phaze 1 according to I. O. Havritukhin and to date it as belonging to the second half of 5th — mid-6th centuries. The settlement was not large; two or three farmsteads could simultaneously exist there. They were located at a distance of 100—150 m from each other.